2003
DOI: 10.5271/sjweh.749
|View full text |Cite
|
Sign up to set email alerts
|

Model for the work-relatedness of low-back pain

Abstract: Objectives This study aimed at developing a model for determining the work-relatedness of low-back pain for a worker with low-back pain using both a personal exposure profile for well-established risk factors and the probability of low-back pain if the worker were unexposed to these factors. Methods After a systematic review of the literature, the pooled prevalence of low-back pain in an unexposed population and the pooled odds ratio (OR) for each risk factor was calculated in a meta-analysis using a random ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
148
2
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(159 citation statements)
references
References 59 publications
4
148
2
5
Order By: Relevance
“…Those with WRMD were asked about 17 occupational elements used in prior studies 15,17,18) . A four-level Likert scale (1: irrelevant, 4: significant meaning) was used to determine the significance of occupational elements in WRMD occurrence.…”
Section: Resultsmentioning
confidence: 99%
“…Those with WRMD were asked about 17 occupational elements used in prior studies 15,17,18) . A four-level Likert scale (1: irrelevant, 4: significant meaning) was used to determine the significance of occupational elements in WRMD occurrence.…”
Section: Resultsmentioning
confidence: 99%
“…With reference to the systems, criteria and diagnostic tools used to recognize LBPD, Lötters [26] aimed to develop a model for determining the work-relatedness of lower back pain for workers with these symptoms, using both personal exposure profiles for well-established risk factors and the probability of lower back pain in the event of no exposure to such factors. To provide information on the level of work-relatedness of LBP, he developed a model based on the epidemiologic information available in the literature.…”
Section: Whole-body Vibration and Professional Diseasesmentioning
confidence: 99%
“…In the Netherlands, since 2005, a rather different system based on the results of Lötters [26] has been used to evaluate the presence of a causal link between working operations and LBP in the event of non-specific lower back pain. As previously described, this probability model is designed as a three-step plan.…”
Section: Whole-body Vibration and Professional Diseasesmentioning
confidence: 99%
“…during lifting, pushing and pulling of objects or working in awkward body positions) are associated with low-back pain (LBP; e.g., Marras et al, 2010;van Dieën et al, 1999). These associations have often been confirmed in epidemiological studies using self-reported exposures or field observations (da Costa and Vieira, 2010;Griffith et al, 2012;Lötters et al, 2003). However, other epidemiological studies did not find support for the association between high low-back loads and LBP, possibly as a result of the lack of appropriate measurement designs (Bakker et al, 2009).…”
Section: Introductionmentioning
confidence: 96%